Oleic acid concentration in bovine adipose tissues: impact on human health, sensory attributes, and genetic regulation - Smith, Stephen B. (Frontiers in Animal Science, 2024)
Fatty acids are important components of foods derived from livestock species, as they contribute to the healthfulness and benefits of beef and beef products. Oleic acid (18:1n-9) is the most highly regulated and most abundant fatty acid in animal tissue. The greatest risk factor for cardiovascular disease (CVD) is low circulating high-density lipoprotein cholesterol (HDL-C), and consumption of beef naturally enriched with oleic acid increases plasma HDL-C concentrations in men and women. Oleic acid is synthesized by the activity of stearoyl-coenzyme A (CoA) desaturase (SCD). In cattle, SCD activity and SCD1 gene expression are highest in adipose tissue depots, followed by skeletal muscle, intestinal mucosa, and the liver. Early studies demonstrated that the concentration of oleic acid beef contributes to positive flavor attributes, but this finding has been difficult to replicate in more recent studies. Including grain (especially corn) in the finishing diets of cattle is essential for the upregulation of SCD1 expression and activity. The measurement of SCD activity is technically difficult, but quantifying SCD gene expression or the concentration of palmitoleic acid (16:1n-7) in beef often provides insight into SCD activity. DNA polymorphisms in SCD1, the sterol regulatory element binding protein-1, the fatty acid synthase, and the growth hormone are associated with oleic acid concentration in the muscle of Japanese Black cattle, indicating a strong genetic component to the regulation of fatty acid composition of beef.